A Note on Aging Characteristics of Polyvinyl, Acetate - U.F. Adhesive Mixtures for Plywood - Shah, R. S. (Indian Forester, 1982)
The note gives the suitability of PVA-UF resin mixtures for plywood making on the basis of the investigations carried out on the aging characteristics of plywood under open atmospheric conditions at room temperature, evaluating its storage life and durability. It has been found that mixtures of PVA-UF having 60 per cent or more UF resin can be used successfully for preparing hot pressed plywood. For cold pressing the mixture should have 70 per cent or more UF resin to get satisfactory results.